MODERN TEACHING METHODS OF TEACHING FOREIGN LANGUAGES - Razzakova , G.R (Innovative Development in Educational Activities, 2023)
This article focuses on productive types of speech activity, which is especially important for mastering a foreign language. The Article specifies how effective work with special texts in a foreign language helps to formulate the necessary language and communication skills for students in a non-native language and promotes the development of their common scientific knowledge and skills.